Determinan pemberian Asi Eksklusif pada Ibu Bekerja di Instansi Pemerintah Kabupaten Bungo Provinsi Jambi - Evi Kristina; Iskandar Syarif; Yuniar Lestari (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
The role of a mother in maintaining a child's health is very important. Knowledge, attitude, motivation, availability of health care facilities, behavior of health workers influence the formation of health behaviors. This study aims to analyze the factors that are related and the most dominant towards exclusive breastfeeding for mothers working in Government Agencies in Bungo Regency. This study uses a combination of quantitative and qualitative research methods. Quantitative research uses cross sectional design. The sample in the quantitative study was 50 mothers who had babies> 6-12 months, while in qualitative research there were 6 in-depth interviews with the heads of the Bungo District Government Agencies. The results of the study obtained the proportion of exclusive breastfeeding as much as 34%. Factors related to breastfeeding are birth attendants and caregiver / family support and the most dominant in exclusive breastfeeding for working mothers is the support of caregivers / family. The scope of exclusive breastfeeding has not reached the target of 80% of the targets set by the Government due to lack of support from Government Agencies, health workers and from caregivers / families. Various efforts are needed to improve the achievement of coverage of exclusive breastfeeding, especially through supporting facilities to support exclusive breastfeeding and the optimization of the role of the Health Office.